2023
DOI: 10.3389/fnins.2023.1093099
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of intracellular calcium signaling in the neurobiology of neurodevelopmental disorders

Abstract: Calcium (Ca2+) comprises a critical ionic second messenger in the central nervous system that is under the control of a wide array of regulatory mechanisms, including organellar Ca2+ stores, membrane channels and pumps, and intracellular Ca2+-binding proteins. Not surprisingly, disturbances in Ca2+ homeostasis have been linked to neurodegenerative disorders, such as Alzheimer’s and Parkinson’s diseases. However, aberrations in Ca2+ homeostasis have also been implicated in neuropsychiatric disorders with a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Moreover, the R451C NLGN3 cultures showed a slower calcium response after depolarization, in comparison to the WT cells. This is in agreement with the dysregulation of Ca 2+ concentration that is associated with several neurodevelopmental disorders, including ASDs 60 . Treatment of NSPCs cultures expressing endogenous R451C NLGN3, with DEX, improved mutant protein levels, both in proliferative and differentiated conditions, confirming the results obtained in the HEK‐293 cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the R451C NLGN3 cultures showed a slower calcium response after depolarization, in comparison to the WT cells. This is in agreement with the dysregulation of Ca 2+ concentration that is associated with several neurodevelopmental disorders, including ASDs 60 . Treatment of NSPCs cultures expressing endogenous R451C NLGN3, with DEX, improved mutant protein levels, both in proliferative and differentiated conditions, confirming the results obtained in the HEK‐293 cells.…”
Section: Discussionsupporting
confidence: 86%
“…This is in agreement with the dysregulation of Ca 2+ concentration that is associated with several neurodevelopmental disorders, including ASDs. 60 This could reflect a higher sensitivity of the NSPCs, where the endogenous mutant protein has a higher impact on the cellular homeostasis and the effect of DEX results in a stronger outcome. Unfortunately, it was not possible to evaluate whether DEX increased the localization of endogenous NLGN3 on the cell surface, therefore favoring the formation of synaptic contacts in differentiated cultures expressing R451C NLGN3, since the endogenous protein is not flag-tagged and there are no commercially available antibodies against NLGN3 to be used in immunostaining.…”
Section: Generation Of Neural Staminal Progenitor Cultures From Adult...mentioning
confidence: 99%
“…Previous studies have shown that the activation of ER stress is associated with the occurrence and development of ASD ( 19 , 21 ). The disruption of neuronal protein homeostasis ( 53 55 ), the dysregulation of calcium homeostasis ( 56 , 57 ), the induction of inflammatory cytokines, such as TNF-α ( 58 , 59 ), IL-33 ( 60 ), and IL-1β ( 61 ), and other pathways have all been proposed as contributing factors ( 59 ). Despite the previous role of ER stress in the pathophysiology of ASD has been highlighted, research on ER stress regulators in the ASD field remains in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown the role of both adaptive and innate immune cells in the etiology of ASD. It was reported that a single injection of IL-6 into pregnant mice led to autism-relevant behaviors in the offspring, while blockade of IL-6 trans-signaling in the brain of mice could cause improved autism-like behavioral symptoms ( 56 , 57 ). Ahmed Nadeem and colleagues revealed that dysregulation in IL-6 receptors is associated with upregulated IL-17A-related signaling in children with autism, and the IL-6/IL-17A-related parameters are positively correlated with disease severity ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SERCA-mediated Ca 2+ dyshomeostasis has been associated with various neuropathological conditions, including bipolar disorder, schizophrenia, Parkinson's disease, Alzheimer's disease, cerebral ischemia and alcoholism (Britzolaki et al, 2018(Britzolaki et al, , 2020. Further, disruption of SERCA and other key endoplasmic reticular Ca 2+ -regulators, such as the inositol triphosphate receptors and ryanodine receptors (RyR), has been implicated in the pathophysiology of autism spectrum disorders and the attention-deficit hyperactivity disorder (ADHD) (Klocke et al, 2023).…”
Section: Introductionmentioning
confidence: 99%